Characterizing biological nitrification inhibition using native Nitrosomonas europaea: mechanism studies and maize cultivar screening - Stanton, Lauren Elizabeth (My University, 2025)
The nitrogen-use efficiency (NUE) of agricultural plants is notoriously poor, typically ranging from 30 to 50%. Ideally, nitrogen (N) fertilizers, primarily applied as ammonium (NH₄⁺), would remain stable to allow optimal uptake by plants. However, NH₄⁺ is rapidly transformed within the soil through a microbial process called nitrification. In this process, ammonia-oxidizing bacteria (AOB), such as Nitrosomonas europaea, oxidize NH₄⁺ and ammonia (NH₃) to nitrite (NO₂⁻), which is further converted to nitrate (NO₃⁻) by nitrite-oxidizing microorganisms and eventually reduced to di-nitrogen (N₂) via denitrification. These processes release nitrous oxide (N₂O) as a by-product, accounting for up to three-quarters of total anthropogenic N₂O emissions in the U.S. N₂O is the third most potent greenhouse gas (GHG) and is also the leading ozone-depleting substance. Therefore, mitigating nitrification is crucial for reducing the environmental impact of agriculture. Recent research has demonstrated that certain plants release phytochemicals through their roots to suppress nitrification, a phenomenon called Biological Nitrification Inhibition (BNI). BNI chemicals disrupt the enzymatic pathways required for nitrification; however, the precise inhibition mechanisms and their impacts on N. europaea remain poorly understood. Previous studies have primarily focused on quantifying BNI activity using recombinant bioluminescent N. europaea due to its heightened sensitivity compared to native strains. However, recombinant strains may not fully represent the behavior and responses of nitrifiers in natural environments. Moreover, their use complicates direct comparisons of BNI effects across studies and conditions, as genetic modifications can introduce confounding factors that do not reflect natural microbial responses. In this study, I systematically evaluated the half-maximal inhibitory concentration (IC50) values and inhibition mechanisms of selected, structurally diverse authentic BNIs including 1,9-Decanediol (1,9-D), Methyl 3-(4-hydroxyphenyl) propionate (MHPP), and Linoleic Acid (LA) on native N. europaea under standardized assay conditions. Synthetic nitrification inhibitor, Allylthiourea (AT), was used as a reference compound. To further expand the application of BNI research beyond microbial studies, I extended my research to maize, aiming to integrate BNI traits into the major agricultural crop. Given that BNI activity varies among plant species and even among cultivars, this study was focused on maize, a significant global crop with substantial potential to improve NUE through targeted breeding. I optimized the BNI activity screening protocol for plants and applied it to evaluate 100 maize germplasm lines, with the goal of identifying cultivars exhibiting the highest BNI activity. By linking physiological traits to BNI potential, this approach lays the groundwork for translating fundamental research into practical applications in agriculture, ultimately supporting the development of sustainable practices that enhance NUE and reduce environmental impact.
Keywords: Nitrosomonas europaea; Nitrification; Biological nitrification inhibition; Protocol optimization; Maize cultivar screening